On Fixed Point Theorems in Intuitionistic Fuzzy Metric Spaces - Zhenhua Jiao (Journal of Applied Mathematics)
The author extends two fixed point theorems (due to Gregori, Sapena, and Žikić, resp.) in fuzzy metric spaces to intuitionistic fuzzy metric spaces.